The Indonesian Lexical Interference in the Students’ Descriptive Writing Texts of Politeknik Negeri Jember - Cholimatus Zuhro; Agus Setia Budi (Journal of English in Academic and Professional Communication, 2023)
This study aimed at analyzing the interference of Indonesian lexical made by   students of Automotive Engineering Study Program of Engineering Department of Politeknik Negeri Jember in their descriptive writing texts. This is a descriptive  study, the data were collected and documented using elicitation teqchnique, and then analyzed by using theory of language interference. This study revealed that there were 40 students made 239 lexical errors in their descriptive writing texts. The identified lexical errors were classified based on their frequencies. From the lexical errors analyzed, the result showed that the category of lexical errors committed by the students in their descriptive writing texts were 5 categories, lexical errors in the form of borrowing (17errors/7%), lexical errors in the form of calque (75 errors/31%) lexical errors in the form of misspelling (72 errors/30%), lexical errors in the form of misselection (53 errors/23%) lexical errors in the form of semantic confusion (22 errors/9%), The students made lexical errors in attempting to follow English sentence construction standards. The differences between the grammatical aspects of the English language and the Indonesian language mean that distinct of lexical errors are committed. The interference of the students' native tongue and their insufficient comprehension of some English grammar rules are to blame for these errors. To construct a decent and acceptable sentence, it is important to teach the students about the distinctions between the two languages' structural differences. The way that topics are handled in Indonesian and English has to be emphasized by the teachers.